New mutation in the mouse Xpd/Ercc2 gene leads to recessive cataracts. - Sarah Kunze; Claudia Dalke; Helmut Fuchs; Matthias Klaften; Ute Rössler; Sabine Hornhardt; Maria Gomolka; Oliver Puk; Sibylle Sabrautzki; Ulrike Kulka; Martin Hrabě de Angelis; Jochen Graw (PLoS ONE, 2015)
Cataracts are the major eye disorder and have been associated mainly with mutations in lens-specific genes, but cataracts are also frequently associated with complex syndromes. In a large-scale high-throughput ENU mutagenesis screen we analyzed the offspring of paternally treated C3HeB/FeJ mice for obvious dysmorphologies. We identified a mutant suffering from rough coat and small eyes only in homozygotes; homozygous females turned out to be sterile. The mutation was mapped to chromosome 7 between the markers 116J6.1 and D7Mit294;4 other markers within this interval did not show any recombination among 160 F2-mutants. The critical interval (8.6 Mb) contains 3 candidate genes (Apoe, Six5, Opa3); none of them showed a mutation. Using exome sequencing, we identified a c.2209T>C mutation in the Xpd/Ercc2 gene leading to a Ser737Pro exchange. During embryonic development, the mutant eyes did not show major changes. Postnatal histological analyses demonstrated small cortical vacuoles; later, cortical cataracts developed. Since XPD/ERCC2 is involved in DNA repair, we checked also for the presence of the repair-associated histone γH2AX in the lens. During the time, when primary lens fiber cell nuclei are degraded, γH2AX was strongly expressed in the cell nuclei; later, it demarcates clearly the border of the lens cortex to the organelle-free zone. Moreover, we analyzed also whether seemingly healthy heterozygotes might be less efficient in repair of DNA damage induced by ionizing radiation than wild types. Peripheral lymphocytes irradiated by 1Gy Cs137 showed 6 hrs after irradiation significantly more γH2AX foci in heterozygotes than in wild types. These findings demonstrate the importance of XPD/ERCC2 not only for lens fiber cell differentiation, but also for the sensitivity to ionizing radiation. Based upon these data, we hypothesize that variations in the human XPD/ERCC2 gene might increase the susceptibility for several disorders besides Xeroderma pigmentosum in heterozygotes under particular environmental conditions.